BCL2 mutations do not confer adverse prognosis in follicular lymphoma patients treated with rituximab. Issue 6 (24th March 2017) - Huet, Sarah; Szafer‐Glusman, Edith; Tesson, Bruno; Xerri, Luc; Fairbrother, Wayne J.; Mukhyala, Kiran; Bolen, Chris; Punnoose, Elizabeth; Tonon, Laurie; Chassagne‐Clément, Catherine; Feugier, Pierre; Viari, Alain; et al.
Abstract: BCL2 mutations have been suggested to confer an adverse prognosis to follicular lymphoma (FL) patients, but their prognostic value has not been assessed in patients treated with a rituximab‐containing regimen. Here we evaluated the prognostic value of BCL2 mutations in a large prospective cohort of 252 patients with FL treated with immunochemotherapy in the PRIMA randomized trial. Using a DNA‐targeted sequencing approach, we detected amino acid altering mutations in 135 patients (54%) and showed that these mutations were probably mediated by the over‐activation of AICDA (activation‐induced cytidine deaminase) in the context of the t(14;18) translocation. The BCL2 variants identified in PRIMA patients affected the BH1, BH2, and BH3 functional motifs at a lower frequency than the N‐terminus and flexible loop domain, with mostly conservative aminoacid changes. With a median follow‐up of 6.7 years, we did not observe any impact of BCL2 mutations either on overall survival or progression‐free survival.